No-go trials can modulate switch cost by interfering with effects of task preparation. - Lenartowicz, A; Yeung, N; Cohen, J (2011)
It has recently been shown that the cost associated with switching tasks is eliminated following 'no-go' trials, in which response selection is not completed, suggesting that the switch cost depends on response selection. However, no-go trials may also affect switch costs by interfering with the effects of task preparation that precede response selection. To test this hypothesis we evaluated switch costs following standard go trials with those following two types of non-response trials: no-go trials, for which a stimulus is presented that indicates no response should be made (Experiment 1); and cue-only trials in which no stimulus is presented following the task cue (Experiment 2). We hypothesized that eliminating no-go stimuli would reveal effects of task preparation on the switch cost in cue-only trials. We found no switch cost following no-go trials (Experiment 1), but a reliable switch cost in cue-only trials (i.e., when no-go stimuli were removed; Experiment 2). We conclude that no-go trials can modulate the switch cost, independent of their effect on response selection, by interfering with task preparation, and that the effects of task preparation on switch cost are more directly assessed by cue-only trials.